2016
DOI: 10.1038/mtna.2016.67
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the Dynamin 2 mRNA by Spliceosome-mediated RNA Trans-splicing

Abstract: Dynamin 2 (DNM2) is a large GTPase, ubiquitously expressed, involved in membrane trafficking and regulation of actin and microtubule cytoskeletons. DNM2 mutations cause autosomal dominant centronuclear myopathy which is a rare congenital myopathy characterized by skeletal muscle weakness and histopathological features including nuclear centralization in absence of regeneration. No curative treatment is currently available for the DNM2-related autosomal dominant centronuclear myopathy. In order to develop thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Among other possible therapeutic strategies ongoing for CNM, a treatment with acetylcholinesterase inhibitor has been reported to lead to improvement of muscle strength in few DNM2‐CNM patients (Gibbs et al , ). We have also previously succeeded to correct the DNM2 mRNA by trans‐splicing, while with a very low efficiency (Trochet et al , ). Targeting DNM2 expression is also of interest beyond the CNM due to DNM2 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Among other possible therapeutic strategies ongoing for CNM, a treatment with acetylcholinesterase inhibitor has been reported to lead to improvement of muscle strength in few DNM2‐CNM patients (Gibbs et al , ). We have also previously succeeded to correct the DNM2 mRNA by trans‐splicing, while with a very low efficiency (Trochet et al , ). Targeting DNM2 expression is also of interest beyond the CNM due to DNM2 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput screens have been utilized in a variety of other studies by applying techniques including sonication to generate robust libraries. 23 , 24 , 29 , 31 , 41 Regardless of screening method, efficiency of trans -splicing continues to be the rate-limiting step for efficacy. Indeed, in another study, repair of Rho showed in vivo trans -splicing and protein production after sub-retinal injection but did not demonstrate phenotypic rescue.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Since then, trans -splicing molecules have been demonstrated with 5′, 3′, or internal exon replacement. 16 , 17 , 18 Pre-mRNA trans -splicing molecules have been demonstrated to edit genes across many disease models including cystic fibrosis, 19 , 20 , 21 , 22 muscular dystrophy, 23 , 24 , 25 hypertrophic cardiomyopathy, 24 , 26 and retinitis pigmentosa 1. 17 Some efforts have also been made to apply trans -splicing to the treatment of cancer cells, including functional repair of p53 in colorectal cancer cells and hepatocellular carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…DNM2-related CNM is a dominant form of CNM potentially due to gain-of-function mutations, and may not be a good target for conventional gene replacement. Reprogramming the Dnm2 RNA to replace the mutated part with a normal sequence was tested in the mouse through spliceosome-mediated RNA trans-splicing [ 91, 92 ]. In this specific example, the classical 3’ trans-splicing strategy led to toxic intermediate.…”
Section: Gene Rna and Enzyme Replacement Strategiesmentioning
confidence: 99%
“…In this specific example, the classical 3’ trans-splicing strategy led to toxic intermediate. However, the alternative usage of 5’ trans-splicing successfully allowed the detection of trans-splicing events at the mRNA and protein levels, both in vitro in fibroblasts and in vivo in WT murine tibialis muscle [ 91 ].…”
Section: Gene Rna and Enzyme Replacement Strategiesmentioning
confidence: 99%